(untitled) (American Journal of Islam and Society, 2006)
Based on 1989 statistics, approximately 131,282 Cham live in Vietnam. They are the descendents of Champa, an Indian-Hindu kingdom that, centuries later, was heavily influenced by Arabic-Islamic culture. Buddhism also made its way into Champa, but was confined to the royal circle during the reign of King Indravarman II (c. 896-905). Historically, the Cham were divided along religious lines: Hindu and Muslim. The Muslim population is subdivided further between the Cham Banis and the mainstream (Sunni) Cham Islam. The Cham population is concentrated mainly in the lowermiddle and southern parts of Vietnam. In the middle part, they live scattered in the Phan Rang and Phan Ri regions. In the southern and southwestern parts, they live in Tay Ninh, Chau Doc, An Giang, Ho Chi Minh City, Long Khanh, and Binh Phuoc cities. The Cham Banis and Cham Hindus only reside in Phan Rang and Phan Ri. There, the Cham Banis make up about onehalf of the Cham population, while the remaining half is Cham Hindu. However, in the south and southwest, all of them follow mainstream Islam ...